Viszontlátás. A túlélés emlékei - Sipos, András (Hungary : MTV2, 1992)
In October 1990 two hundred elderly Jewish women travel to Allendorf, Germany. Allendorf has been part of the Buchenwald concentration camp during the 2nd World War. The visit brings back the still vivid 45 year-old memories of the deportation and forced labor. The former inmates of the camps tell their stories about the brutality of the SS and gendarme; the indifference of the Hungarians; the murdering of their loved ones; their lives in the yellow star houses and in the ghetto; and the details of the tortures they suffered during their deportation and in the concentration camps.
The film was screened at yellow-star-houses series '10 documentary films about the persecution of Jews' in 2014.
Yellow Star Houses Film Program 2014
Keywords: Documentary films